Manufacturing method for improving strength of permanent magnetic ferrite wet-pressing magnetic shoe

By using coarse-grained iron red and controlling fine abrasive particle size greater than 0.8 μm, the compressive strength and temperature resistance of permanent magnet ferrite magnet tiles are improved, and the problem of insufficient compressive strength of magnetic tiles in the prior art is solved, ensuring the stability and efficient performance of magnetic tiles.

CN119661210APending Publication Date: 2025-03-21BEIKUANG MAGNETS FUYANG CO LTD

Patent Information

Application Number
CN202411722162.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the compressive strength of permanent magnet ferrite tiles, resulting in the magnetic tiles being easily broken or broken during magnetization or use, affecting the normal operation of the motor.

Method used

By using coarse grain iron red in the preparation of prefixed materials and controlling the fine grinding size to be greater than 0.8 μm during the fine grinding stage, the temperature resistance of the product is improved, the brittleness of the product is reduced, and the compressive strength of the magnetic tiles is improved.

Benefits of technology

It significantly improves the compressive strength and temperature resistance of permanent magnet ferrite magnetic tiles, reduces the brittleness of magnetic tiles, and ensures the stability of magnetic tiles under high pressure and high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661210A_ABST
    Figure CN119661210A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of insect situation forecasting lamps, in particular to a manufacturing method for improving the strength of a permanent magnetic ferrite wet-pressing magnetic shoe. Comprising the following production steps: 1, weighing iron oxide red with proper granularity, strontium carbonate with proper granularity and an additive, uniformly mixing, and pre-sintering to obtain pre-sintered material magnetic powder; 2, putting the pre-sintered material magnetic powder and a sintering aid into a ball mill, and performing micro-crushing by taking water as a medium; 3, the water content of the micro-crushed slurry is adjusted, the slurry is placed in a magnetic field to be formed, and a magnetic shoe pressed blank is obtained; and 4, sintering the magnetic tile pressed blank in a kiln to obtain a sintered magnetic tile semi-finished product. And 5, grinding the sintered magnetic shoe semi-finished product. According to the method, iron oxide red with the particle size larger than or equal to 1.5 micrometers is adopted for producing the ferrite pre-sintering material, meanwhile, the fine grinding particle size of slurry before wet pressing forming is controlled to be larger than 0.8 micrometer, and then the mechanical strength of the wet pressing magnetic shoe obtained through forming and sintering is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of permanent ferrite processing, and more specifically, to a manufacturing method for improving the strength of wet-pressed magnetic tiles of permanent ferrite. Background Art

[0002] Permanent ferrite magnets are the core materials for manufacturing high-efficiency and energy-saving permanent magnet motors. They can achieve efficient energy conversion and are of great significance for improving motor efficiency and achieving energy conservation and emission reduction. They are widely used in new energy vehicles, white appliances, smart manufacturing and other fields. Due to the needs of rotating motor design, whether as stators or rotors, permanent ferrite magnets are mostly designed in the shape of tiles, referred to as magnetic tiles. A permanent magnet DC motor requires at least 2 pieces and at most dozens of permanent ferrite tiles.

[0003] With the increasing demand for miniaturization and energy saving of permanent magnet motors, the performance requirements of permanent ferrite magnet tiles are getting higher and higher, and the volume, especially the thickness requirements are getting smaller and smaller. Therefore, under the same conditions, the requirements for the compressive strength of the tiles are getting higher and higher. If the mechanical strength is not enough, the tiles may be broken or fractured during magnetization or use when installed on the motor, which will cause the motor rotor to get stuck, resulting in more serious consequences. Therefore, the mechanical strength of the tiles must be controlled during the production process to ensure that the strength of the tiles meets the requirements.

[0004] China's patent application CN118073077A discloses a processing method for improving the mechanical strength of magnetic tiles. The method improves the mechanical strength of magnetic tiles by controlling the molding process parameters, including: magnetic tile pressing time, water absorption vacuum degree; controlling the sintering process parameters, including: magnetic tile loading method, kiln feeding speed; controlling the grinding process parameters, including: grinding speed, grinding wheel drive motor output frequency.

[0005] China's patent application CN115028442A improves the fluidity of the slurry by controlling the particle size distribution of the slurry and adding a homemade liquid dispersant to the ferrite slurry before magnetic field forming, thereby improving the density consistency of the magnetic tile blank, making the shrinkage rate of each point of the blank tend to be consistent during the sintering process, reducing surface tension, and avoiding the expansion of microcracks caused by surface tension, ultimately improving the compressive strength of the magnetic tile product and reducing magnetic tile cracking.

[0006] The invention patent with publication number CN102738974A discloses a method for increasing the compressive strength of tile-shaped magnets for permanent magnet motors, which is characterized in that the tile-shaped magnets are installed in a refractory bowl or directly on a refractory material support plate, and the compressive mechanical properties of the magnets are improved by controlling the heating, insulation and cooling curves.

[0007] Chinese patent application CN1959868A discloses a process for adding a fluidity improver to permanent magnet ferrite slurry, thereby reducing the resistance of the slurry during wet molding, improving the magnetic domain orientation during molding, reducing the water content of the molded body, and improving the body strength, and ultimately improving the strength and magnetic properties of the rare earth permanent magnet ferrite after sintering;

[0008] China's patent application CN112645705A discloses a process for improving the bending resistance limit of permanent ferrite magnetic tile devices, which is mainly achieved by controlling the particle size distribution of the slurry after ball milling, the grouting speed during magnetic field forming, and the number of grinding wheels during the grinding process, so as to improve the bending strength of the magnetic tile without reducing the magnetic properties. The specific process parameters given in the patent include slurry particle size distribution D0.10: 0.4-0.6μm, D0.50: 0.8-1.0μm, D0.90: 1.9-2.0μm; the single cavity grouting flow rate of the mold is 15-40mm / s; the number of grinding wheels used in the grinding process is 150-400 mesh.

[0009] The above patents propose methods to improve the strength of permanent ferrite tiles from the perspectives of material formulation, improving slurry fluidity, particle size distribution, pressing, sintering, grinding and other processes. These are detailed improvements in the conventional production process of permanent ferrites, and do not fundamentally target the core factors that affect the strength of tiles for research and improvement.

[0010] Therefore, in order to meet the increasingly stringent requirements of the current permanent magnet ferrite tiles for compressive strength, a preparation method for improving the compressive strength of the permanent magnet ferrite tiles is urgently needed. Summary of the invention

[0011] In order to overcome the above-mentioned defects of the prior art, an embodiment of the present invention provides a manufacturing method for improving the strength of wet-pressed permanent ferrite magnetic tiles to solve the problems raised in the above-mentioned background technology.

[0012] To achieve the above object, the present invention provides the following technical solution: a method for improving the strength of wet-pressed permanent ferrite magnetic tiles, comprising the following production steps:

[0013] Step 1: weigh iron oxide red with appropriate particle size, strontium carbonate with appropriate particle size and additives, mix them evenly and then pre-sinter them to obtain pre-sintered magnetic powder;

[0014] Step 2: Put the pre-sintered magnetic powder together with the sintering aid into a ball mill and grind it into small pieces using water as the medium;

[0015] Step 3: adjusting the water content of the slurry after micro-crushing, placing it in a magnetic field for molding, and obtaining a magnetic tile pressed green body;

[0016] Step 4: Place the magnetic tile pressed green sheet in a kiln for sintering to obtain a sintered magnetic tile semi-finished product.

[0017] Step 5: Grinding the sintered magnetic tile semi-finished product to obtain a permanent magnet ferrite magnetic tile finished product;

[0018] Step 6: Randomly sample several magnetic tile products for compressive strength testing.

[0019] In a preferred embodiment, in step 1, iron oxide red with a particle size greater than 1.5 μm, strontium carbonate with a particle size greater than 1.5 μm, and additives are weighed.

[0020] In a preferred embodiment, in step 2, the degree of pulverization of the pre-sintered magnetic powder is such that the particle size of the fine pulverization is greater than 0.8 μm, more preferably greater than 0.9 μm.

[0021] In a preferred embodiment, in step three, the water content of the slurry after fine grinding is adjusted to 40±2wt%.

[0022] In a preferred embodiment, in step five, the sintered magnetic tile semi-finished product is ground using a multi-station grinder.

[0023] In a preferred embodiment, in step six, the appearance of the magnetic tile products is inspected, various defective products are removed and the yield rate is calculated, and finally random sampling is performed.

[0024] In a preferred embodiment, in step three, the magnetic field strength is 8000 Oe and the molding pressure is 8 MPa.

[0025] In a preferred embodiment, in step 4, the sintering furnace parameters are a heating rate of 6°C / min, a sintering temperature of 1200°C, and a heat preservation time of 2 hours, followed by natural cooling to room temperature to obtain a semi-finished magnetic tile.

[0026] In a preferred embodiment, in step six, a universal testing machine is used to test the ultimate compressive strength of the magnetic tile, and the impact speed is 1 m / s.

[0027] Technical effects and advantages of the present invention:

[0028] The present invention adopts coarse-grained iron red in the preparation of pre-sintered materials; at the same time, the fine grinding particle size is controlled to be greater than 0.8 μm in the fine grinding stage, so that the temperature resistance of the product is significantly improved, the product is not prone to crystallization, the brittleness of the product is greatly reduced, and the strength of the product is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a graph showing the compressive ultimate strength test results of the magnetic tile products of Example 1 and Comparative Examples 1-3 of the present invention;

[0030] Figure 2This is a graph showing the temperature resistance test results of the magnetic tile products of Example 1 and Comparative Examples 1-3 of the present invention;

[0031] Figure 3 The graph is a test result of the compressive ultimate strength of the magnetic tile products of Example 1 and Comparative Examples 4-7 of the present invention;

[0032] Figure 4 This is a graph showing the temperature resistance test results of the magnetic tile products of Example 1 and Comparative Examples 4-7 of the present invention;

[0033] Figure 5 This is a graph showing the compressive ultimate strength test results of the magnetic tile product of Example 2 of the present invention;

[0034] Figure 6 This is a graph showing the temperature resistance test results of the magnetic tile product in Example 2 of the present invention. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Reference Figure 1-Figure 6 :

[0037] Example 1

[0038] Step 1: Select the particle size of iron oxide red to be 1.63μm and the particle size of strontium carbonate to be 1.56μm. According to the molecular formula SrFe 12 O 19 , weigh iron red and strontium carbonate, and add SiO2 at 0.2% of the total weight, mix well and pre-sinter at 1300°C to obtain pre-sintered magnetic powder.

[0039] Step 2: Put the pre-sintered magnetic powder together with the sintering aid into a ball mill and grind it into powder with water as the medium. The particle size is controlled at 0.83 μm.

[0040] Step 3: Control the moisture content of the slurry after fine grinding to 40±2wt%, place it in a magnetic field for molding, apply a magnetic field, press and mold, the magnetic field strength is 8000Oe, the molding pressure is 8MPa, and obtain a magnetic tile green sheet;

[0041] Step 4: Place the magnetic tile pressed green sheet in a sintering furnace for sintering at a heating rate of 6°C / min and a sintering temperature of 1200°C. Keep the temperature for 2 hours and cool the green sheet naturally to room temperature to obtain a magnetic tile semi-finished product.

[0042] Step 5: Grinding the sintered magnetic tile semi-finished product using a multi-station grinder to obtain a permanent magnet ferrite magnetic tile finished product;

[0043] Step 6: Randomly sample 10 magnetic tile products produced and use a universal testing machine to test the ultimate compressive strength of the magnetic tiles at an impact speed of 1m / s.

[0044] Test results such as Figure 1 As shown, the temperature resistance test results are as follows Figure 2 shown.

[0045] Comparative Example 1

[0046] Step 1: Select the particle size of iron oxide red to be 1.63μm and the particle size of strontium carbonate to be 1.56μm. According to the molecular formula SrFe 12 O 19 , weigh iron red and strontium carbonate, and add SiO2 at 0.2% of the total weight, mix well and pre-sinter at 1300°C to obtain pre-sintered magnetic powder.

[0047] Step 2: Put the pre-sintered magnetic powder together with the sintering aid into a ball mill and grind it into powder with water as the medium. The particle size is controlled at 0.71 μm.

[0048] Step 3: Control the moisture content of the slurry after fine grinding to 40±2wt%, place it in a magnetic field for molding, apply a magnetic field, press and mold, the magnetic field strength is 8000Oe, the molding pressure is 8MPa, and obtain a magnetic tile green sheet;

[0049] Step 4: Place the magnetic tile pressed green sheet in a sintering furnace for sintering at a heating rate of 6°C / min and a sintering temperature of 1200°C. Keep the temperature for 2 hours and cool the green sheet naturally to room temperature to obtain a magnetic tile semi-finished product.

[0050] Step 5: Grinding the sintered magnetic tile semi-finished product using a multi-station grinder to obtain a permanent magnet ferrite magnetic tile finished product;

[0051] Step 6: Randomly sample 10 magnetic tile products produced and use a universal testing machine to test the ultimate compressive strength of the magnetic tiles at an impact speed of 1m / s.

[0052] Test results such as Figure 1 The temperature resistance test results are shown in Figure 2 shown.

[0053] Comparative Example 2

[0054] Step 1: Select the particle size of iron oxide red to be 1.05μm and the particle size of strontium carbonate to be 1.07μm. According to the molecular formula SrFe 12 O 19, weigh iron red and strontium carbonate, and add SiO2 at 0.2% of the total weight, mix well and pre-sinter at 1300°C to obtain pre-sintered magnetic powder.

[0055] Step 2: Put the pre-sintered magnetic powder together with the sintering aid into a ball mill and grind it into powder with water as the medium. The particle size is controlled at 0.83 μm.

[0056] Step 3: Control the moisture content of the slurry after fine grinding to 40±2wt%, place it in a magnetic field for molding, apply a magnetic field, press and mold, the magnetic field strength is 8000Oe, the molding pressure is 8MPa, and obtain a magnetic tile green sheet;

[0057] Step 4: Place the magnetic tile pressed green sheet in a sintering furnace for sintering at a heating rate of 6°C / min and a sintering temperature of 1200°C. Keep the temperature for 2 hours and cool the green sheet naturally to room temperature to obtain a magnetic tile semi-finished product.

[0058] Step 5: Grinding the sintered magnetic tile semi-finished product using a multi-station grinder to obtain a permanent magnet ferrite magnetic tile finished product;

[0059] Step 6: Randomly sample 10 magnetic tile products produced and use a universal testing machine to test the ultimate compressive strength of the magnetic tiles at an impact speed of 1m / s.

[0060] Test results such as Figure 1 As shown, the temperature resistance test results are as follows Figure 2 shown.

[0061] Comparative Example 3

[0062] Step 1: Select the particle size of iron oxide red as 1.05μm and the particle size of strontium carbonate as 1.07μm. According to the molecular formula SrFe12O19, weigh iron oxide red and strontium carbonate, add SiO2 at 0.2% of the total weight, mix well, and pre-sinter at 1300℃ to obtain pre-sintered magnetic powder.

[0063] Step 2: Put the pre-sintered magnetic powder together with the sintering aid into a ball mill and grind it into powder with water as the medium. The particle size is controlled at 0.71 μm.

[0064] Step 3: Control the moisture content of the slurry after fine grinding to 40±2wt%, place it in a magnetic field for molding, apply a magnetic field, press and mold, the magnetic field strength is 8000Oe, the molding pressure is 8MPa, and obtain a magnetic tile green sheet;

[0065] Step 4: Place the magnetic tile pressed green sheet in a sintering furnace for sintering at a heating rate of 6°C / min and a sintering temperature of 1200°C. Keep the temperature for 2 hours and cool the green sheet naturally to room temperature to obtain a magnetic tile semi-finished product.

[0066] Step 5: Grinding the sintered magnetic tile semi-finished product using a multi-station grinder to obtain a permanent magnet ferrite magnetic tile finished product;

[0067] Step 6: Randomly sample 10 magnetic tile products produced and use a universal testing machine to test the ultimate compressive strength of the magnetic tiles at an impact speed of 1m / s.

[0068] Test results such as Figure 1 The temperature resistance test results are shown in Figure 2 shown.

[0069] Comparative Example 4

[0070] Step 1: Select the particle size of iron oxide red to be 1.63 μm, the particle size of strontium carbonate to be 1.07 μm, weigh iron oxide red and strontium carbonate according to the molecular formula SrFe12O19, add SiO2 at 0.2% of the total weight, mix well, and pre-sinter at 1300°C to obtain pre-sintered magnetic powder;

[0071] Step 2: Put the pre-sintered magnetic powder together with the sintering aid into a ball mill and grind it into powder with water as the medium. The particle size is controlled at 0.83 μm.

[0072] Step 3: Control the moisture content of the slurry after fine grinding to 40±2wt%, place it in a magnetic field for molding, apply a magnetic field, press and mold, the magnetic field strength is 8000Oe, the molding pressure is 8MPa, and obtain a magnetic tile green sheet;

[0073] Step 4: Place the magnetic tile pressed green sheet in a sintering furnace for sintering at a heating rate of 6°C / min and a sintering temperature of 1200°C. Keep the temperature for 2 hours and cool the green sheet naturally to room temperature to obtain a magnetic tile semi-finished product.

[0074] Step 5: Grinding the sintered magnetic tile semi-finished product using a multi-station grinder to obtain a permanent magnet ferrite magnetic tile finished product;

[0075] Step 6: Randomly sample 10 magnetic tile products produced and use a universal testing machine to test the ultimate compressive strength of the magnetic tiles at an impact speed of 1m / s.

[0076] Test results such as Figure 3 The temperature resistance test results are shown in Figure 4 shown.

[0077] Comparative Example 5

[0078] Step 1: Select iron oxide red with a particle size of 1.63 μm and strontium carbonate with a particle size of 1.07 μm. According to the molecular formula SrFe12O19, weigh iron oxide red and strontium carbonate, add SiO2 at 0.2% of the total weight, mix well, and pre-sinter at 1300°C to obtain pre-sintered magnetic powder.

[0079] Step 2: Put the pre-sintered magnetic powder together with the sintering aid into a ball mill and grind it into powder with water as the medium. The particle size is controlled at 0.71 μm.

[0080] Step 3: Control the moisture content of the slurry after fine grinding to 40±2wt%, place it in a magnetic field for molding, apply a magnetic field, press and mold, the magnetic field strength is 8000Oe, the molding pressure is 8MPa, and obtain a magnetic tile green sheet;

[0081] Step 4: Place the magnetic tile pressed green sheet in a sintering furnace for sintering at a heating rate of 6°C / min and a sintering temperature of 1200°C. Keep the temperature for 2 hours and cool the green sheet naturally to room temperature to obtain a magnetic tile semi-finished product.

[0082] Step 5: Grinding the sintered magnetic tile semi-finished product using a multi-station grinder to obtain a permanent magnet ferrite magnetic tile finished product;

[0083] Step 6: Randomly sample 10 magnetic tile products produced and use a universal testing machine to test the ultimate compressive strength of the magnetic tiles at an impact speed of 1m / s.

[0084] Test results such as Figure 3 The temperature resistance test results are shown in Figure 4 shown.

[0085] Comparative Example 6

[0086] Step 1: Select the particle size of iron oxide red to be 1.05 μm, the particle size of strontium carbonate to be 1.56 μm, weigh iron oxide red and strontium carbonate according to the molecular formula SrFe12O19, add SiO2 at 0.2% of the total weight, mix well, and pre-sinter at 1300°C to obtain pre-sintered magnetic powder;

[0087] Step 2: Put the pre-sintered magnetic powder together with the sintering aid into a ball mill and grind it into powder with water as the medium. The particle size is controlled at 0.83 μm.

[0088] Step 3: Control the moisture content of the slurry after fine grinding to 40±2wt%, place it in a magnetic field for molding, apply a magnetic field, press and mold, the magnetic field strength is 8000Oe, the molding pressure is 8MPa, and obtain a magnetic tile green sheet;

[0089] Step 4: Place the magnetic tile pressed green sheet in a sintering furnace for sintering at a heating rate of 6°C / min and a sintering temperature of 1200°C. Keep the temperature for 2 hours and cool the green sheet naturally to room temperature to obtain a magnetic tile semi-finished product.

[0090] Step 5: Grinding the sintered magnetic tile semi-finished product using a multi-station grinder to obtain a permanent magnet ferrite magnetic tile finished product;

[0091] Step 6: Randomly sample 10 magnetic tile products produced and use a universal testing machine to test the ultimate compressive strength of the magnetic tiles at an impact speed of 1m / s.

[0092] Test results such as Figure 3 The temperature resistance test results are shown in Figure 4 shown.

[0093] Comparative Example 7

[0094] Step 1: Select the particle size of iron oxide red as 1.05μm and the particle size of strontium carbonate as 1.56μm. According to the molecular formula SrFe12O19, weigh iron oxide red and strontium carbonate, add SiO2 at 0.2% of the total weight, mix well, and pre-sinter at 1300℃ to obtain pre-sintered magnetic powder.

[0095] Step 2: Put the pre-sintered magnetic powder together with the sintering aid into a ball mill and grind it into powder with water as the medium. The particle size is controlled at 0.71 μm.

[0096] Step 3: Control the moisture content of the slurry after fine grinding to 40±2wt%, place it in a magnetic field for molding, apply a magnetic field, press and mold, the magnetic field strength is 8000Oe, the molding pressure is 8MPa, and obtain a magnetic tile green sheet;

[0097] Step 4: Place the magnetic tile pressed green sheet in a sintering furnace for sintering at a heating rate of 6°C / min and a sintering temperature of 1200°C. Keep the temperature for 2 hours and cool the green sheet naturally to room temperature to obtain a magnetic tile semi-finished product.

[0098] Step 5: Grinding the sintered magnetic tile semi-finished product using a multi-station grinder to obtain a permanent magnet ferrite magnetic tile finished product;

[0099] Step 6: Randomly sample 10 magnetic tile products produced and use a universal testing machine to test the ultimate compressive strength of the magnetic tiles at an impact speed of 1m / s.

[0100] Test results such as Figure 3 The temperature resistance test results are shown in Figure 4 shown.

[0101] Example 2

[0102] Step 1: Select the particle size of iron oxide red to be 1.63μm and the particle size of strontium carbonate to be 1.56μm. According to the molecular formula SrFe 12 O 19 , weigh iron oxide red and strontium carbonate, add SiO2 at 0.2% of the total weight, mix well, and pre-sinter at 1300°C to obtain pre-sintered magnetic powder;

[0103] Step 2: Put the pre-sintered magnetic powder together with the sintering aid into a ball mill and grind them into powder using water as the medium. The particle sizes are controlled at 0.60 μm, 0.71 μm, 0.83 μm, 0.92 μm and 1.05 μm respectively.

[0104] Step 3: Control the moisture content of the slurry after fine grinding to 40±2wt%, place it in a magnetic field for molding, apply a magnetic field, press and mold, the magnetic field strength is 8000Oe, the molding pressure is 8MPa, and obtain a magnetic tile green sheet;

[0105] Step 4: Place the magnetic tile pressed green sheet in a sintering furnace for sintering at a heating rate of 6°C / min and a sintering temperature of 1200°C. Keep the temperature for 2 hours and cool the green sheet naturally to room temperature to obtain a magnetic tile semi-finished product.

[0106] Step 5: Grinding the sintered magnetic tile semi-finished product using a multi-station grinder to obtain a permanent magnet ferrite magnetic tile finished product;

[0107] Step 6: Randomly sample 10 magnetic tile products produced and use a universal testing machine to test the ultimate compressive strength of the magnetic tiles at an impact speed of 1m / s.

[0108] Test results such as Figure 5 The heat resistance test results are shown in Figure 6 shown.

[0109] Finally: The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for improving the strength of wet pressed permanent ferrite magnetic tiles, characterized in that; The production process includes the following steps: Step 1: weigh iron oxide red with appropriate particle size, strontium carbonate with appropriate particle size and additives, mix them evenly and then pre-sinter them to obtain pre-sintered magnetic powder; Step 2: Put the pre-sintered magnetic powder together with the sintering aid into a ball mill and grind it into small pieces using water as the medium; Step 3: adjusting the water content of the slurry after micro-crushing, placing it in a magnetic field for molding, and obtaining a magnetic tile pressed green body; Step 4: Place the magnetic tile pressed green sheet in a kiln for sintering to obtain a sintered magnetic tile semi-finished product. Step 5: Grinding the sintered magnetic tile semi-finished product to obtain a permanent magnet ferrite magnetic tile finished product; Step 6: Randomly sample several magnetic tile products for compressive strength testing.

2. A method for improving the strength of wet pressed permanent ferrite magnetic tiles according to claim 1, characterized in that: In step 1, iron oxide with a particle size greater than 1.5 μm, strontium carbonate with a particle size greater than 1.5 μm, and additives are weighed.

3. The method for improving the strength of wet pressed permanent ferrite magnetic tiles according to claim 1, characterized in that: In step 2, the pre-sintered magnetic powder is pulverized to a degree that the particle size of the fine pulverization is greater than 0.8 μm, more preferably greater than 0.9 μm.

4. The method for improving the strength of wet pressed permanent ferrite magnetic tiles according to claim 1, characterized in that: In step 3, the water content of the slurry after fine grinding is adjusted to 40±2wt%.

5. The method for improving the strength of wet pressed permanent ferrite magnetic tiles according to claim 1, characterized in that: In step five, the sintered magnetic tile semi-finished product is ground using a multi-station grinder.

6. The method for improving the strength of wet pressed permanent ferrite magnetic tiles according to claim 1, characterized in that: In step six, the appearance of the magnetic tile products is inspected, various defective products are removed and the yield rate is calculated, and finally random sampling is carried out.

7. A method for improving the strength of wet pressed permanent ferrite magnetic tiles according to claim 4, characterized in that: In step three, the magnetic field strength is 8000 Oe and the molding pressure is 8 MPa.

8. The method for improving the strength of wet-pressed permanent ferrite magnetic tiles according to claim 1, characterized in that: In step 4, the sintering furnace parameters are a heating rate of 6°C / min, a sintering temperature of 1200°C, and a heat preservation time of 2 hours. The furnace is naturally cooled to room temperature to obtain a semi-finished magnetic tile.

9. A method for improving the strength of wet pressed permanent ferrite magnetic tiles according to claim 6, characterized in that: In step six, a universal testing machine is used to test the ultimate compressive strength of the magnetic tile, with an impact speed of 1 m / s.

Citation Information

Patent Citations

  • Method for increasing compressive strength of tile-shaped magnet for permanent magnet motor

    CN102738974A

  • Process method capable of improving breaking limit of permanent magnetic ferrite magnetic shoe device

    CN112645705A

  • Preparation method for improving compressive strength of permanent magnetic ferrite magnetic tile

    CN115028442A

  • Processing method for improving mechanical strength of magnetic shoe

    CN118073077A

  • Method for raising intensity of rare earth permanent magnet ferrite, and magnetic characteristic

    CN1959868A

Cited By

  • Magnetic shoe mold for improving mechanical strength of permanent magnetic ferrite and implementation method of magnetic shoe mold

    CN121246005A